Effects of nonsurgical periodontal therapy in patients with moderately controlled type 2 diabetes mellitus and chronic periodontitis in Nepalese population - Goel K; Pradhan S; Bhattarai MD (Dove Medical Press, 2017)
Khushboo Goel,1 Shaili Pradhan,2 Madhur Dev Bhattarai3 1Department of Periodontology and Oral Implantology, College of Dental Surgery, B.P. Koirala Institute of Health Sciences, Dharan, 2Department of Dental Surgery, Periodontics Unit, Bir Hospital, 3Nepal Diabetes Association, Kathmandu, Nepal Objectives: Despite several investigations, evidence is still controversial regarding the effect of periodontal treatment on diabetes. This study evaluates and compares the effect on glycemic control and periodontal status with or without nonsurgical periodontal therapy in patients with type 2 diabetes mellitus and chronic periodontitis in a Nepalese population. Materials and methods: A total of 82 patients attending the diabetes clinic and fulfilling enrollment criteria with moderate to severe periodontitis were selected. They were assigned in an alternative sequence, into test and control group. Both groups were instructed to continue with their medical treatment without modifications. Scaling and root surface debridement were performed in the test group whereas the control group received oral hygiene instructions with no treatment during the 3-month study period. Results: There were 41 participants in each group with the mean age of 50.66±7.70 and 53.80±9.16 years, average diabetes duration of 6.32±4.21 and 6.24±4.00 years, mean body mass index of 24.78±1.85 and 24.6±1.79 kg/m2, and glycated hemoglobin (HbA1c) level of 6.71±0.50% and 6.80±0.45%, in the test and control group, respectively. After 3 months, there was significant reduction in HbA1c levels in the test group compared to the control group (p=0.029). Clinical periodontal parameters of gingival index, probing depth (PD), and clinical attachment level (CAL) significantly improved in the test group (p<0.001) with PD reduction by 0.9 mm and gain in CAL by 0.3 mm compared to the control group (p>0.001) who showed an increase by 0.05 mm. Conclusion: This study showed that nonsurgical periodontal therapy may have a beneficial effect on HbA1c level in moderately controlled type 2 diabetic patients. Keywords: glycated, hemoglobin A, inflammation, periodontal disease, periodontal debridement, therapy